2000
DOI: 10.1080/096708700227499
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and phytotoxicity of multiple petroleum oil sprays on sweet orange (Citrus sinensis (L.)) and pummelo (C. grandis (L.)) in Southern China

Abstract: Abs tract. The efficacy of pest control of three different oil formulations in multiple low-concentration spray programmes on sweet orange and pummelo were compared with unsprayed and normal farmer-treatments over three years. Phytotoxicity of sprays was assessed in terms of fruit and leaf drop, fruit yield and external fruit quality. Trees sprayed with any type of oil had lower pest numbers than unsprayed trees. On sweet orange, the heaviest oil was better than the normal farm practice at controlling chaff sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Fortunately, it has been found that natural enemies of scale and some other pest insects are conserved if mineral oils are used (Walker & Aitken, 1996; Rae et al , 2000). Thus there is the opportunity to use IPM that combines biological control and intervention with mineral oils when necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, it has been found that natural enemies of scale and some other pest insects are conserved if mineral oils are used (Walker & Aitken, 1996; Rae et al , 2000). Thus there is the opportunity to use IPM that combines biological control and intervention with mineral oils when necessary.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that PSO had no negative effect on the fruit quality and yield. Previous field studies (Rae et al 1996(Rae et al , 2000Huang et al 1998) also found no evidence of phytotoxicity caused by narrow range oil (C21, C23 and C27) on sweet orange trees. On the contrary, PSO could generally improve the external quality of fruit over time (Rae et al 2000).…”
Section: Discussionmentioning
confidence: 81%
“…With the development of optimized formulations, modern petroleum oils are more effective against pests and less phytotoxic than their predecessors. Studies in Australia (Beattie et al 1995a) and in China showed that the narrow-range oil did not cause any phytotoxicity to citrus trees (Rae et al 1996(Rae et al , 2000Huang et al 1998). Their use is advocated by the International Organic Agriculture Organization.…”
Section: Introductionmentioning
confidence: 96%
“…Petroleum-based horticultural mineral oils (HMOs) control citrus leafminer, Phyllocnistis citrella Stainton (Lepidoptera: Gracillariidae), red scale, Aonidiella aurantii (Maskell) (Hemiptera: Diaspididae), chaff scale, Parlatoria pergandii Comstock spiny whitefly, Aleurocanthus spiniferus (Quaintance) (Hemiptera: Aleyrodidae) and ACP in citrus Davidson, 1991;Rae et al, 1996Rae et al, , 1997Rae et al, , 2000. Most HMOs are relatively inexpensive, have low mammalian toxicity, little residual activity, and are relatively harmless to beneficial insects (Stansly et al, 2002).…”
Section: Introductionmentioning
confidence: 99%